Evaluasi Sistem Informasi Manajemen Puskesmas (SIMPUS) Menggunakan Metode National Usability-Focused Health Information System Scale (NUHISS): Studi di Puskesmas Bunguran Tengah - Arlette Suzy Puspa Pertiwi; Ign. Wiseto P. Agung; Hetria Hayyun Namirah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The digitalization of healthcare services in Indonesia has shown significant progress. At the primary healthcare level, one form of digitalization is the implementation of the Puskesmas Management Information System (SIMPUS), which aims to facilitate fast, accurate, and reliable information delivery by healthcare personnel. However, various usability-related challenges have emerged in its implementation. This study aimed to evaluate SIMPUS using the National Usability-Focused Health Information System Scale (NUHISS) method, with a case study conducted at Bunguran Tengah Public Health Center, Natuna Regency, Riau Islands Province, during March–April 2025. A descriptive method with a qualitative approach was employed. Participants included physicians, nurses, midwives, laboratory technicians, pharmacists, and medical record officers. Data were collected through interviews, observations, and document reviews, and analyzed using the Miles and Huberman model. The findings revealed that SIMPUS demonstrated adequate technical stability. However, system issues such as automatic logouts, data-saving failures, and information loss were still present. Although the system's response time was generally good, unexpected behaviors—such as disappearing menus, unsaved data, and inter-module inconsistencies—were found to disrupt workflow and increase the risk of service errors. Consistent data loss was also reported, although not on a daily basis. These issues led to service delays, additional administrative workload, and potential risks to patient safety. Users addressed these problems by manually recording or re-entering data, coordinating with technical teams, and conducting repeated verifications to ensure information accuracy.